A Comparison of Factors Related to University Students’ Learning: College-Transfer and Direct-Entry from High School Students - Acai, Anita; Newton, Genevieve (Canadian Journal of Higher Education, 2015)
Articulation agreements between colleges and universities, whereby students with two-year college diplomas can receive advancement toward a four-year university degree, are provincially mandated in some Canadian provinces and highly encouraged in others. In this study, we compared learning in college-transfer and direct-entry from high school (DEHS) students at the University of Guelph–Humber in Ontario, using eight factors related to learning: age, gender, years of prior postsecondary experience, learning approach, academic performance, use of available learning resources, subjective course experience, and career goals. Our results show that while college-transfer students tend to be older than DEHS students, they do not significantly differ in either learning approach or academic performance. This is an important finding, suggesting that college-transfer programs are a viable option for non-traditional university students. We conclude that the academic success of college-transfer students is attainable with careful consideration of policies, such as admissions criteria, and the drafting of formal articulation agreements between institutions.